2006
DOI: 10.1080/09687860600831539
|View full text |Cite
|
Sign up to set email alerts
|

Defining the roles of Asn-128, Glu-129 and Phe-130 in loop A of the 5-HT3receptor

Abstract: The ligand binding pocket of Cys-loop receptors consists of a number of binding loops termed A-F. Here we examine the 5-HT 3 receptor loop A residues Asn-128, Glu-129 and Phe-130 using modelling, mutagenesis, radioligand binding and functional studies on HEK 293 cells. Replacement of Asn-128 results in receptors that have wild type [ 3 H]granisetron binding characteristics but large changes (ranging from a five-fold decrease to a 1500-fold increase) in the 5-HT EC 50 when compared to wild type receptors. Phe-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
7
31
0
Order By: Relevance
“…Y148 has been the object of mutation studies ( Thompson et al, 2005;Venkataraman et al, 2002;Yan & White, 2005): it has been proposed to play a role in both receptor function and ligand binding. Interestingly, all the residues which in our model interact with Y148 (Y138 and W85, W178 and L179) underwent experimental mutations (see Table 1): the results for W178 were discussed previously and support its primary role in the interface stabilization (Beene et al, 2002;Reeves et al, 2003;Spier & Lummis, 2000;Thompson et al, 2005Thompson et al, , 2008; W85 was shown to be important for ligand binding Spier & Lummis, 2000;Sullivan et al, 2006;Thompson et al, 2005;Yan & White, 2005), as it will be discussed in the details further on; the results of experimental alanine scanning mutagenesis studies on Y138 demonstrated its involvement in receptor structure and function Thompson et al, 2005;Venkataraman et al, 2002) and evidences from experimental studies on mutants of L179 seem to support its involvement in channel opening (Thompson et al, 2005. As a whole, these seem to have both structural and functional roles.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Y148 has been the object of mutation studies ( Thompson et al, 2005;Venkataraman et al, 2002;Yan & White, 2005): it has been proposed to play a role in both receptor function and ligand binding. Interestingly, all the residues which in our model interact with Y148 (Y138 and W85, W178 and L179) underwent experimental mutations (see Table 1): the results for W178 were discussed previously and support its primary role in the interface stabilization (Beene et al, 2002;Reeves et al, 2003;Spier & Lummis, 2000;Thompson et al, 2005Thompson et al, , 2008; W85 was shown to be important for ligand binding Spier & Lummis, 2000;Sullivan et al, 2006;Thompson et al, 2005;Yan & White, 2005), as it will be discussed in the details further on; the results of experimental alanine scanning mutagenesis studies on Y138 demonstrated its involvement in receptor structure and function Thompson et al, 2005;Venkataraman et al, 2002) and evidences from experimental studies on mutants of L179 seem to support its involvement in channel opening (Thompson et al, 2005. As a whole, these seem to have both structural and functional roles.…”
supporting
confidence: 66%
“…H180 is supposed to be involved in receptor binding and function: its mutations cause changes in agonist binding but not in antagonist binding and the H180-mutated receptor is not functional ; similarly, also L179 is supposed to be involved in subunit rotation and conformational modification occurring during opening of the channel . In addition, W178 is also adjacent to two other null spot residues, E124 and F125 are also considered to be relevant for receptor function (Boess et al, 1997;Price et al, 2008;Sullivan et al, 2006;Thompson et al, 2005Thompson et al, , 2008. As a whole, combining the information from CASM and experimental mutagenesis, the interface pattern W116-H180-L179-W178-E124-F125 seems to define a pathway (or part of a more extended pathway) of residues involved in protein conformational transitions upon ligand binding, triggering receptor activation.…”
Section: Residues Involved In Coupling Ligand Binding To Channel Gatingmentioning
confidence: 96%
See 2 more Smart Citations
“…In loop A, N128 also points towards the binding site, but consistent with the absence of specific interactions with the equivalent residue in 2YME (Y91), the affinity of granisetron was not altered. In previous work, a similar absence of effects on granisetron has also been reported for range of other substitutions at this location (Price et al., 2008, Sullivan et al., 2006). However, the effects of N128C we measured on the affinity of tropisetron (7-fold) and previous reports of changes to the EC 50 of 5-HT, m CPBG and the binding affinity of VUF10166 suggests that effects may depend upon the ligand studied (Price et al., 2008, Sullivan et al., 2006, Thompson et al., 2014).…”
Section: Discussionmentioning
confidence: 99%